Radical Into the Impact of Investment and Debt Default on Enterprises and Reflections: To ofo bike as an example - Guo, Shuqian (International Journal of Global Economics and Management, 2024)
This paper analyzes the specific case of ofo bicycle to study the relationship between enterprise overinvestment and debt default, and draws out the impact of both on the enterprise. This paper first analyzes the main situation of the enterprise, including the operation situation and financing situation, etc.; then study the enterprise’s non-fixed asset investment and fixed asset investment respectively, and through the comparison of the growth rate of fixed assets and the growth rate of sales revenue, conclude that there is overinvestment in the enterprise; thereafter, this paper analyzes the development history of the enterprise and the default situation, and draws the conduction process of the enterprise’s overinvestment and debt default. Through the case study, this paper concludes that the senior management problem and the market situation of the enterprise lead to overinvestment, and overinvestment and senior management’s insensitivity to liabilities will cause the enterprise’s debt default.